2003
DOI: 10.1016/s0032-3861(03)00686-4
|View full text |Cite
|
Sign up to set email alerts
|

Direct UV photocrosslinking of poly(N-vinyl-2-pyrrolidone) (PVP) to produce hydrogels

Abstract: Hydrogels for biomedical purposes, made from synthetic polymers as starting materials and free of co-adjuvant molecules, have been produced almost exclusively by high-energy radiative processes. On the other hand, UV photocrosslinking of such materials has been used in conjunction of monomers and/or photoinitiators. This work was addressed to the analysis of poly(N-vinyl-2-pyrrolidone) (PVP) submitted to direct photocrosslinking in aqueous solution, using low pressure Hg lamp (l em ¼ 254 nm). The process effic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
83
1
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(93 citation statements)
references
References 10 publications
3
83
1
2
Order By: Relevance
“…The photopolymerization is used in biomedical applications due to its ability to convert a liquid monomer or macromer into a crosslinked network. Another advantage of this procedure is associated with the reduction of possible residual organic solvents involved during the polymerization process [9][10]. In order to obtain the crosslinked network, chemical crosslinking is presented as a highly useful method for creating hydrogels with good mechanical stability [11].…”
Section: Introductionmentioning
confidence: 99%
“…The photopolymerization is used in biomedical applications due to its ability to convert a liquid monomer or macromer into a crosslinked network. Another advantage of this procedure is associated with the reduction of possible residual organic solvents involved during the polymerization process [9][10]. In order to obtain the crosslinked network, chemical crosslinking is presented as a highly useful method for creating hydrogels with good mechanical stability [11].…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogel dressings have attracted much attention among researchers for their use in the medicinal field, chiefly in the healing of burn wounds. It must be emphasized here that there are already numerous natural and synthetic polymers being studied and/or applied as medicinal hydrogels, and PVP is among them [24,25]. But, beyond PVP as a unique polymer, other polymer systems involving VP-monomers are also used in this application area: chemically modified PVP [26][27][28], copolymers containing units of N-vinyl-2-pyrrolidone in their chains for example, poly(methacrylamide-co-N-vinyl-2-pyrro-lidone-co-itaconic acid) [29]; poly(N-vinyl-2-pyrrolidone-co-styrene) [30]; poly(N-vinyl-2-pyrrolidone-coacrylic acid), [31] and blends of PVP with other biocompatible polymers (for example, PVP-CMC [32]; PVP-PVA [33]; PVP-k-carrageenan [34]; PVP-chitosan [35].…”
Section: Introductionmentioning
confidence: 99%
“…In this work, two different techniques of hydrogel attainment were used: one from mixtures of acid aqueous co-solutions of chitosan and PVP, of which the resultant films and solutions were afterwards irradiated by ultraviolet radiation (λ = 254 nm), that is capable of inducing cross-linking of PVP by recombination of free macroradicals and subsequent hydrogel formation [25,17]; another from the reaction of poly (N-vinyl-2-pyrrolidoneco-acrolein) a novel copolymer synthesized in our biomaterials laboratory and chitosan. Cross-linking, in this case, is supposed to occur through Schiff base formation by the aldehyde group of the acrolein units of the copolymer and available amine groups of chitosan [68].…”
Section: Introductionmentioning
confidence: 99%
“…irradiation subsequent to polymerization) is used in many variations to create interpolymer networks (e.g. to produce hydrogels directly from polymer solutions (Lopergolo et al 2003)) and control the morphology and properties of polymer blends, membranes etc. (He et al 2009;Tran-Cong et al 1991).…”
Section: A) Uv Irradiation (Photo-crosslinking)mentioning
confidence: 99%
“…Since benzophenone is only slightly soluble in water, radical formation on the microgel components is expected to be assisted by water radiolysis. It has been reported that in aqueous solutions UV irradiation generates hydrogen atoms and hydroxyl radicals from water molecules (Janata 2002;Lopergolo et al 2003). These water hydroxyl radicals can react with polymers bearing photo-reactive species, and thus generate macroradicals (Lopergolo et al 2003).…”
Section: A) Uv Irradiation (Photo-crosslinking)mentioning
confidence: 99%